Mocarna duchem zmartwychwstańskim. Alicja Kotowska CR – zakonnica, nauczycielka, męczenniczka, błogosławiona - Pyszna, Joanna (Warszawskie Studia Teologiczne, 2021)
The article presents the hero silhouette of blessed Alice Kotowska – the nun of the Congregation of the Sisters of the Resurrection, the superior of the community in Wejherowo and the secondary school principal. Because of her involvement in religious, social and patriotic activities, at the end of October in 1939, she was arrested by the Nazis and soon shot in the forests of Piaśnica. She was one of the tens of thousands of victims of the Pomeranian Crime. Account for her saintly life and the suffered death at the hand of the occupant, she was exalted to the glory of alters in 1999 among 108 Polish martyrs of World War II.